Purchasing behavior and use of digital sports offers by CrossFit® and weightlifting athletes during the first SARS-CoV-2 lockdown in Germany - Nicole Meier; Till Nägler; Robin Wald; Annette Schmidt (BMC, 2022)
Abstract Background To combat the spread of SARS-CoV-2, CrossFit® training centers, and fitness studios were closed during the first lockdown in Germany from mid-March until June 2020, and as a result, CrossFit® (CFA) or weightlifting athletes (WLA) faced a major challenge for the first time. Therefore, this study aimed to investigate the impact of the first lockdown on the training behavior and to analyze the way the athletes dealt with the new situation. In detail, we focus on habits of purchase and examine the acceptance of digital sports offers between CFA and WLA in response to the restrictions of the nationwide lockdown. Methods An online survey was used to characterize the purchasing behavior and use of digital sports offers of CFA and WLA. In total, 484 volunteers (192 women, 290 men, 2 diverse) responded to the online questionary, allowing us to identify changes in training behavior and differences between the sports disciplines. Results Our data shows both CFA and WLA purchase new equipment for a home gym and the use of digital sports increased significantly across all age groups. A comparison during the lockdown even showed that within the CFA, one group (n = 142) reported losing 5 kg or more of body mass, while the value of the WLA remained constant. On the one hand, the results indicate that despite the restrictions during the lockdown, CFA were may able to enhance health aspects by improving their body composition. On the other hand, this study shows that the training habits of both groups of athletes have changed significantly with the use of digital sports offers. Conclusions We suppose that the great openness and the expansion of online sports offers during the first lockdown may change the sports industry in the future.